2017
DOI: 10.1002/wcms.1314
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dimensional half‐metallic materials: theoretical simulations and design

Abstract: Spintronics, which uses the spin of electrons for information processing, is viewed as one of the most promising next-generation information technology with high speed and low energy consumption. To generate pure spins for subsequent spin transport and manipulation, a half-metallic material with 100% spin polarization around the Fermi level is highly desired. Half metal features a unique electronic structure, with one spin channel metallic while keeping the other spin channel insulating. In order to minimize t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 100 publications
0
46
0
Order By: Relevance
“…They all possess half‐metallic band structures, in which spin‐up bands intersect with Fermi levels presenting metallic behaviors, while bandgaps arise for the spin‐down bands, leading to 100% spin polarization percentage. The completely spin‐polarized character is rare in natural low‐dimensional materials, and it is beneficial for improving the efficiency of spin‐polarized injection. A key parameter determining such performance is the half‐metal gap, which is defined as the minimum of the difference between Fermi level and the bottom of spin‐down conduction bands and the difference between Fermi level and the top of spin‐down valence bands.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They all possess half‐metallic band structures, in which spin‐up bands intersect with Fermi levels presenting metallic behaviors, while bandgaps arise for the spin‐down bands, leading to 100% spin polarization percentage. The completely spin‐polarized character is rare in natural low‐dimensional materials, and it is beneficial for improving the efficiency of spin‐polarized injection. A key parameter determining such performance is the half‐metal gap, which is defined as the minimum of the difference between Fermi level and the bottom of spin‐down conduction bands and the difference between Fermi level and the top of spin‐down valence bands.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that long‐range ferromagnetic (FM) orderings in layered materials (CrI 3 and Cr 2 Ge 2 Te 6 ) remain stable down to 2D limit below their Curie temperatures (45 K for CrI 3 monolayer and 30 K for Cr 2 Ge 2 Te 6 bilayer), which draws great interest in seeking other 2D ferromagnets with high critical temperature for practical applications. On the other hand, half‐metallic materials, featuring one spin channel metallic and the other insulating, could supply fully polarized spin carriers, which makes them attractive for pure spin generation, injection, and transport . Until now, most of studied half‐metals are introduced by external defects or charge doping .…”
Section: Introductionmentioning
confidence: 99%
“…Herein, the 2D van der Waals (vdW) materials, like graphene (Castro Neto, Guinea, Peres, Novoselov, & Geim, ; Novoselov et al, ), transition‐metal dichalcogenide (Radisavljevic, Radenovic, Brivio, Giacometti, & Kis, ) and phosphorene (Li et al, ; Liu et al, ), with atomic thickness, high mobility, and high on/off ratio when used as transistors, are promising candidates to replace the current semiconductor materials in microelectronic devices that sustain the Moore's Law for longer times. Nevertheless, it is even more challenging to achieve 2D FM semiconductors (Feng et al, ; Li & Wu, ; Li & Yang, ; Tang, Zhou, & Chen, ; Zhang et al, ) compared with 3D (three‐dimensional) DMS because doping magnetic ions into 2D materials like graphene or phosphorene is much more difficult than replacing Ga in GaAs or Zn in ZnO by 3 d magnetic ions like Cr or Mn. Meanwhile, the saturation magnetization, along with the magnetic anisotropy energy, would be much lower (Wu, Zeng, & Jena, ) than 3 d magnetism in 3D DMS.…”
Section: Introductionmentioning
confidence: 99%
“…However, the magnetism in these metal‐free materials suffers from stability problem due to their vanishing MAEs and has rarely been observed in experiment. Note that the well‐ known 1D sandwich organometallic wires, such as [TMBz] ∞ and [TMCp] ∞ , are predicted as ferromagnetic (half) metals rather than semiconductors . Thus, 1D ferromagnetic semiconductors with large MAEs still remain blank.…”
Section: Background and Originality Contentmentioning
confidence: 99%